A Good public transport system must be easy and convenient to use, fast, safe, clean and affordable - Kyte, Rachael (2012)
Sees the need to balance affordability for passengers with long-term economic viability of tranporation services. Stresses the importance of choosing the right transport system. Notes that there is litte value in a city opting for a high-cost system if a smaller, less expensive one could do the job.